Analysis Of Audit Fee Determinants In Manufacturing Companies In Indonesia Stock Exchange - Magdalena Lasniroha; Unggul Purwohedi; Dwi Handarini (Jurnal Akuntansi, Perpajakan dan Auditing, 2022)
This study's objective is to investigate and offer empirical evidence concerning the impact of the Independent  Board  of  Commissioners,  Company  Profitability,  Company  Complexity, Company  Risk,  and  Internal  Audit  Function  on  Audit  Fee.  In  this  study,  the  population comprised of 153 Manufacturing Companies listed between 2017 and 2019 on the Indonesia Stock Exchange (IDX). In addition, the number of observations in this study comprised of 78 observations  from  26  manufacturing  companies  listed  on  the  IDX  between  2017  and  2019, which were selected based on the sample selection criteria and the outcomes of theclassical assumption  test.  Multiple  regression  equations  were  used  to  examine  the  study's  data.  Audit fees  were  not  significantly  affected  by  independent  commissioners,  company  risk,  or  the internal  audit  function.  It  is  evident  from  these  data  that  the  auditor's  determination  of  the magnitude  of  the  audit  fee  is  influenced  by  the  firm's  level  of  profitability  and  complexity; consequently, the company must consider its complexity and financial performance to ensure that the audit fees it pays are suitable